Why So Many People Are Overweight and Obese Today—A Finnish Perspective - Maria Hofman-Bergholm (Obesities)
An increasingly obese population has spread worldwide. But what causes so many people to be overweight or obese? Obesity is also one of the most significant public health problems in Finland, as the obesity rate in Finland has increased over the past two decades and is now much higher than the EU average, with every second Finn classified as at least overweight. Finland will be used as a case study, as we have been monitoring the fitness and body weight of Finnish recruits annually since the 1970s and therefore have comprehensive reliable data to use for the period. This article will review existing reports in the fields of obesity and societal development focusing on the Nordic countries. As far as possible, different social phenomena will be discussed in separate sections to try to find out if there is something in societal development that could be a major cause of this obesity epidemic. This article will also give some suggestions on what could be done in the future to slow down the negative trend.